The energy loss and nuclear absorption effects in semi-inclusive deep inelastic scattering on nucleus. (11th January 2018) - Song, Li-Hua; Xin, Shang-Fei; Liu, Na
Abstract: Semi-inclusive deep inelastic lepton-nucleus scattering provides a good opportunity to investigate the cold nuclear effects on quark propagation and hadronization. Considering the nuclear modification of the quark energy loss and nuclear absorption effects in final state, the leading-order computations on hadron multiplicity ratios for both hadronization occurring outside and inside the medium are performed with the nuclear geometry effect of the path length L of the struck quark in the medium. By fitting the HERMES two-dimensional data on the multiplicity ratios for positively and negatively charged pions and kaons produced on neon, the hadron–nucleon inelastic cross section σ h for different identified hadrons is determined, respectively. It is found that our predictions obtained with the analytic parameterizations of quenching weights based on BDMPS formalism and the nuclear absorption factor N A ( z, ν ) are in good agreement with the experimental measurements. This indicates that the energy loss and nuclear absorption are the main nuclear effects inducing a reduction of the hadron yield for quark hadronization occurring outside and inside the nucleus, respectively.